Physical, chemical and sensorial profile of creamy cream cheese obtained from different coagulants (Research, Society and Development, 2021)
The inclusion of sensory analysis helps in the perception of acceptance of food consumption, some factors are identified with various methods, as in the present study, the objective was to evaluate the sensory and rheological properties of creamy curd obtained from pasta coagulated by acetic acid, citric and lactic. For sensory analysis, two steps were adopted, the first by surveying 32 descriptive terms of the attributes: appearance, aroma, texture and flavor, applying the Check-All-That-Apply method (CATA), in the second stage the acceptance tests were carried out for the attributes, determined by the structured hedonic scale of seven points and intention to purchase scale of five points. The applied methodologies made it possible to identify the most relevant attributes of the sensory properties of creamy curd. For the statistical data of the sensorial analyzes Cochran's Q test was used, determined by the p-Value at 5% of significance and correspondence analysis, performed by the computer program R (R Core Team version 3.6.3). Values of creamy curd were identified, which provided the results of 21 attributes.